2011
DOI: 10.1177/0884533611418783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Different Intravenous Fat Emulsions in Patients With Systemic Inflammatory Response Syndrome and Sepsis

Abstract: Fish oil-based fat emulsions might have anti-inflammatory and hepatoprotective effects in hyperinflammatory disease such as sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…Most of the studies were focused on middle-aged surgical or critically ill patients. Seven (44%) of the 16 studies found some positive results for LETs or liver ultrasound tests in patients receiving IVLEs containing FO (8,11,12,15,16,19,21). Studies using FO in doses of ≥ 0.150 mg/kg/day presented more positive results than those with lower doses.…”
Section: Potential Benefits Prevention Of Alterations In Liver Enzymementioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies were focused on middle-aged surgical or critically ill patients. Seven (44%) of the 16 studies found some positive results for LETs or liver ultrasound tests in patients receiving IVLEs containing FO (8,11,12,15,16,19,21). Studies using FO in doses of ≥ 0.150 mg/kg/day presented more positive results than those with lower doses.…”
Section: Potential Benefits Prevention Of Alterations In Liver Enzymementioning
confidence: 99%
“…Several prospective studies have been published assessing the preventive effect of IVLEs containing FO on alterations in LETs or PNALD (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Characteristics of these studies are shown in table I.…”
Section: Potential Benefits Prevention Of Alterations In Liver Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…A third-generation lipid emulsion containing soybean, medium-chain triglyceride, olive and fish oils (SMOFlipid) resulted in favorable FA profiles (a desirable reduction in the ω-6/ω-3-FA ratio) 95 and retained hepatocellular integrity. 96 Small trials showed that fish oil-(ω-3) supplemented PN had anti-inflammatory and hepatoprotective effects in hyperinflammatory disease such as sepsis, 97 a beneficial effect on PN-associated liver disease, 98 reduced the Acute Physiology and Chronic Health Evaluation (APACHE) II and Simplified Acute Physiology Score II, as well as procalcitonin in sepsis. 92 However, clearly larger trials are required to confirm the findings or form the basis for recommendations in practice.…”
Section: Omega-3 Fatty Acids (Anti-inflammatory Nutrients)mentioning
confidence: 99%